2015
DOI: 10.1111/pbi.12371
|View full text |Cite
|
Sign up to set email alerts
|

ASNP‐based consensus genetic map for synteny‐based trait targeting in faba bean (Vicia fabaL.)

Abstract: SummaryFaba bean (Vicia faba L.) is a globally important nitrogen‐fixing legume, which is widely grown in a diverse range of environments. In this work, we mine and validate a set of 845 SNPs from the aligned transcriptomes of two contrasting inbred lines. Each V. faba SNP is assigned by BLAST analysis to a single Medicago orthologue. This set of syntenically anchored polymorphisms were then validated as individual KASP assays, classified according to their informativeness and performance on a panel of 37 inb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
187
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(210 citation statements)
references
References 50 publications
17
187
0
Order By: Relevance
“…The distribution of E-values based on BLASTN results of the comparator reference legume species to the generated faba bean assemblies is summarised in The results of the comparison of Doza (Table S5) and Farah (Table S6) transcriptome assemblies to the previously published faba bean transcriptome sets (from Webb et al [29] and Kaur et al [22]) revealed that the current assemblies captured approximately 96% of transcripts from the Webb et al [29] datasets and approximately 98% of contigs and 78% of singletons from the Kaur et al [22] study. A total of 25.7% and 35.4% transcripts were found to be specific to the Doza and Farah transcriptome assemblies, respectively, based on comparison to the previously-published faba bean datasets.…”
Section: Classification and Functional Annotation Of The Faba Bean Trmentioning
confidence: 99%
See 4 more Smart Citations
“…The distribution of E-values based on BLASTN results of the comparator reference legume species to the generated faba bean assemblies is summarised in The results of the comparison of Doza (Table S5) and Farah (Table S6) transcriptome assemblies to the previously published faba bean transcriptome sets (from Webb et al [29] and Kaur et al [22]) revealed that the current assemblies captured approximately 96% of transcripts from the Webb et al [29] datasets and approximately 98% of contigs and 78% of singletons from the Kaur et al [22] study. A total of 25.7% and 35.4% transcripts were found to be specific to the Doza and Farah transcriptome assemblies, respectively, based on comparison to the previously-published faba bean datasets.…”
Section: Classification and Functional Annotation Of The Faba Bean Trmentioning
confidence: 99%
“…The reciprocal read mapping of Farah to Doza showed that 81.2% of Farah-derived transcripts exhibited matches to Doza-derived sequences. Furthermore, an overall comparison results of Farah versus Doza in addition to the datasets from Kaur et al [22] and Webb et al [29] studies are summarised in Figure 2. This identified a total of 8428 Doza-specific transcripts, 9437 Farah-specific transcripts and 9572 transcripts common to both the assemblies that was not previously characterised in Vicia faba L. datasets.…”
Section: Classification and Functional Annotation Of The Faba Bean Trmentioning
confidence: 99%
See 3 more Smart Citations